A computerised notation and analysis system in soccer - Nader, R.; Lees, A.; Reilly, T. (International Journal of Computer Science in Sport, 2002)
Soccer is associated with a high rate of injury (Dvorak and Junge, 2000; Rahnama et al., 2002b). For prevention of injury, risk factors should be identified and notation analysis is helpful for identifying precursors to injury (Reilly, 1993). Notation analysis and associated computerised systems can provide an accurate and objective evaluation of game characteristics, including injury and associated risk. Hand notation systems represent the simplest form of behaviour analysis and have been used for many years. Reilly and Thomas (1976) employed a motion analysis system in order to estimate the work-rates of soccer players. Since then, hand notation has been complemented by computerised methods of analysis for the rapid processing of data. For example, McGarry and Franks (1995) used a computer-based system for notational analysis to create models of the game and to identify winning tactics. There has been no serious attempt to design a definitive notation analysis system for assessing injury or injury risk in soccer. A new hand notation method for analysis of injury and injury risk has recently been introduced by Rahnama et al. (2002a). This method was found to take a long time to record and analyse data and led to the design of a novel computerised system. The system designed can be modified to enable rapid collection and analysis of data for a wide range of sports injury contexts. The aim of this report, therefore is, to describe and explain the computerised notation and analysis system that is designed for analysing injury and injury risk in soccer.